2005
DOI: 10.1093/jmedent/42.1.63
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Bovine Arboviruses fromCulicoidesBiting Midges (Diptera: Ceratopogonidae) in Southern Japan: 1985–2002

Abstract: In 1985--2002, surveillance for bovine arboviruses was conducted in Kagoshima, located in the most southern part of the main islands of Japan and known to be an area where bovine arboviral diseases have frequently been epidemic. Culicoides biting midges were collected in a cowshed by light traps. A total of 456,300 Culicoides biting midges representing 13 species were collected, and a portion of each pool of midges were tested for virus isolation. Overall, 85 isolates of six different viruses were obtained fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(58 citation statements)
references
References 21 publications
3
53
0
Order By: Relevance
“…Molecular identification of C. oxystoma is of great importance as this species is the most important potential vector of several arboviruses in Japan, with 85.9% of all viruses isolated from this species causing major livestock diseases, such as EHDV [35]. It would therefore be interesting to determine whether this important potential vector species plays a role in the epidemiology of Culicoides -borne diseases in Israel and the Middle East.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Molecular identification of C. oxystoma is of great importance as this species is the most important potential vector of several arboviruses in Japan, with 85.9% of all viruses isolated from this species causing major livestock diseases, such as EHDV [35]. It would therefore be interesting to determine whether this important potential vector species plays a role in the epidemiology of Culicoides -borne diseases in Israel and the Middle East.…”
Section: Discussionmentioning
confidence: 99%
“…2 weeks) during the BTV season, it showed the highest mean period between blood meals as well as the highest range of expectation to remain infective, suggesting that this species could serve as an important augmenting vector during that limited period. Although previous attempts to isolate arboviruses from pools of midges of the C. schultzei complex from Israel have been mainly unsuccessful [39], studies from other countries have demonstrated the isolation of arboviruses from this species complex [14], [35]. In addition, BTV was shown to multiply in an Israeli C. schultzei gp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The other insects were pooled on the basis of place and species, and stored at −80°C until virus isolation. The collected insects were processed for virus isolation with BHK-21 cells as described previously [24]. …”
Section: Methodsmentioning
confidence: 99%
“…The S RNA segment encodes the nucleocapsid (N) protein and a smaller nonstructural (NSs) protein in overlapping reading frames. The AKAV is transmitted principally by Culicoides biting midges [14, 26, 30], and it is widely distributed from the tropical to temperate zones of the world, except for the Americas [21]. The AKAV causes Akabane disease when susceptible pregnant cattle, sheep and goats are infected [21].…”
mentioning
confidence: 99%